2009
DOI: 10.1098/rspb.2009.1266
|View full text |Cite
|
Sign up to set email alerts
|

Symbiosis-dependent gene expression in coral–dinoflagellate association: cloning and characterization of a P-type H+-ATPase gene

Abstract: We report the molecular cloning of a H þ -ATPase in the symbiotic dinoflagellate, Symbiodinium sp. previously suggested by pharmacological studies to be involved in carbon-concentrating mechanism used by zooxanthellae when they are in symbiosis with corals. This gene encodes a protein of 975 amino acids with a calculated mass of about 105 kDa. The structure of the protein shows a typical Ptype H þ -ATPase structure (type IIIa plasma membrane H þ -ATPases) and phylogenetic analyses show that this new proton pum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 56 publications
0
53
0
Order By: Relevance
“…2), suggesting that the regions with the brighter LSG signal are due to increased VHA activity. The pH of the symbiosome lumen did not neutralize in the presence of bafilomycin after 30 min, indicating that either more time was required to reach neutral pH or an additional mechanism(s), such as the symbiosis-dependent Symbiodinium P-type H + -ATPase (25), may contribute to acidification of the algal microenvironment.…”
Section: Resultsmentioning
confidence: 99%
“…2), suggesting that the regions with the brighter LSG signal are due to increased VHA activity. The pH of the symbiosome lumen did not neutralize in the presence of bafilomycin after 30 min, indicating that either more time was required to reach neutral pH or an additional mechanism(s), such as the symbiosis-dependent Symbiodinium P-type H + -ATPase (25), may contribute to acidification of the algal microenvironment.…”
Section: Resultsmentioning
confidence: 99%
“…This VAT is present in many membranes of organelles and also frequently in the plasma membranes of renal cells or osteoclasts [70]. VAT is therefore a good candidate for transferring protons to plasma in the hen uterine glandular cell, especially as this VAT was revealed in other species producing CaCO 3 biominerals and shown to export H + during mineralisation [71,72]. This proton ATPase extrudes H + across the basolateral membrane of pancreatic duct epithelium [57] which is secreting high amounts of HCO 3 - using mechanisms quite similar to uterine glandular cells.…”
Section: Discussionmentioning
confidence: 99%
“…While yet to be applied for larval studies, symbiosis-specific genes have been identified recently in Aiptasia anemones (Bucher et al, 2016;Wolfowicz et al, 2016). From the symbiont perspective, apart from the identification of protein kinases that may be involved in the establishment of symbiosis (Rosic et al, 2014), a symbiosisspecific gene was identified in Symbiodinium clade A, an H + -ATPase (Bertucci et al, 2010). This gene is the only symbiosisspecific gene that had its expression verified in Symbiodinium associated with invertebrate larvae (Mies et al, 2017b,c).…”
Section: Biochemical and Molecular Relationshipmentioning
confidence: 99%